Sazonalidade do índice de conforto térmico para a bovinocultura leiteira em 3 municípios da região sul do Amazonas - Prado, Sayra Oikawa (2023)
Agricultural production has grown in recent years, mainly in the northern region of Brazil. Amazonas has been making room for this activity, mainly in the south of the state, where dairy production is on the rise. To ensure the success of dairy farming, it is essential to consider the interaction between the animal and the environment in which it is raised. In this way, it is essential that animal thermal comfort is taken into account to increase production efficiency. In this sense, the objective of this work was to evaluate the seasonality of THI, for dairy cattle, in 3 municipalities of Amazonas. The research was carried out in the southern mesoregion of the state of Amazonas, focusing on the municipalities of Apuí, Boca do Acre, and Humaitá in neutral years (2013) and under the influence of El Niño (2015) and La Niña (2022). Precipitation (Ppt), air temperature (Ta) and dew point temperature (Tpo) data for calculating the Temperature and Humidity Index (ITU) were collected from the server of The European Center for Medium-Range Weather Forecasts (ECMWF). The data were processed with Python 3.9 programming language by writing scripts and using the Pandas, Numpy, Xarray libraries and later had the graphs plotted. The research results revealed that, among the municipalities analyzed, Boca do Acre obtained the best animal thermal comfort indexes, while Humaitá presented the highest animal thermal discomfort index in the three years studied. The Temperature and Humidity Indexes were within the animal thermal comfort threshold only for the years of neutrality (2013) and under the effect of La Ninã (2022), only in the municipality of Boca do Acre during the Amazonian summer.